Photo‐responsive nanozymes: Mechanism, activity regulation, and biomedical applications. Issue 1 (16th October 2020) - Wang, Chaohui; Wang, Hongyu; Xu, Bolong; Liu, Huiyu
Abstract: Nanozyme is defined as a nanomaterial‐based artificial enzyme. It has rapidly attracted interest and been regarded as a promising alternative to natural enzymes due to its low cost, high stability, and high activity. Many researchers have recently paid attention to the optical properties of nanozymes and have found a variety of nanozymes with excellent photoactivity, called photo‐responsive nanozymes. In this minireview, we briefly introduce the mechanisms of photo‐responsive nanozymes, especially for the relationship between the enzyme‐like activity and photoactivity. Some activity regulation strategies for improving the performance of photo‐responsive nanozymes are also summarized. Moreover, the synergy of enzyme‐like activity and photoactivity in biomedical applications will also be discussed, including cancer therapy, antibacteria, and biological detection. We believe this minireview will be of great significance for understanding the optical properties of nanozymes and applying them in biomedicine. Abstract : In this Mini‐Review, the authors have briefly discussed the action mechanisms of enzyme‐like activity and photoactivity, focusing on the relationship between enzyme‐like characteristics and optical performances of nanozymes (photo‐enhanced, photo‐activated, and photo‐synergistic relation). The authors also summarize the activity regulation strategies for improving the performances of photo‐responsive nanozymes, highlight the synergy of enzyme‐like activity and photoactivity in some biomedical applications, including cancer therapy, antibacteria, and biological detection.